An exploration of biosimilar TNF-alpha inhibitors uptake determinants in hospital environments in Italy, Portugal, and Spain - Barcina Lacosta, Teresa; Vulto, Arnold G.; Huys, Isabelle; Simoens, Steven (Frontiers in Medicine, 2023)
Background The availability of biosimilar medicines in Southern European markets has allowed purchasing biologics at a lower cost for healthcare systems. However, the capacity to seize this cost-reduction opportunity in the long run depends on fostering a sustainable competitive environment for all the market players involved. Diverse policies and information campaigns have been launched in Italy, Portugal and Spain to support uptake of “best-value” biologics (BVB). Despite these measures, the utilization of lower-cost biologics in certain regions is low, especially when it comes to the treatment of chronic conditions. Objective We aim to identify biosimilar uptake determinants in hospital environments in Italy, Portugal and Spain, using the class of TNF-alpha inhibitors as an example. Methods This is a mixed-methods study based on (1) the quantitative analysis of regional uptake data for TNF-alpha inhibitor biosimilars and (2) the qualitative processing of semi-structured interviews capturing experts’ views on uptake determinants for biosimilars. Results The organization of multi-stakeholder information campaigns supporting TNF-alpha inhibitor biosimilars use in Italy, Portugal and Spain has resulted in an increased familiarity of healthcare professionals and patients with the prescription/use of these products. However, barriers persist that impede high biosimilars uptake, especially in chronic patient populations eligible for a switch. These are: (1) the late publication of position statements on biosimilars interchangeability by regulatory health authorities; (2) the vague positioning of (national/regional) health authorities on best switching practices (including multiple biosimilar-to-biosimilar switches); (3) the existence of policy frameworks that do not necessarily support the initiation of switching protocols; (4) the establishment of sometimes inefficient purchasing procedures that limit biosimilars potential to compete for market shares. Diverse approaches taken regionally to address these barriers have contributed to heterogeneous TNF-alpha inhibitor biosimilars uptake across Southern Europe. Conclusion Our research signaled the limited reach of biosimilar policies implemented locally, if not supported by a national policy framework. This study highlights the need for the coordinated implementation of policy measures fostering biosimilars use at the regional and national level in Italy, Portugal and Spain. These measures should account for the particularities of off-patent biologic and biosimilar markets and should jointly address supply- and demand-side challenges.